Propagation Law of Cracks in Surrounding Rock of Different Shape Tunnels Under Adjacent Blasting - LIU Kang, GUO Dongming, ZHANG Shuai, SHI Zhenxin, CHEN Jin (Meikuang Anquan, 2020)
To understand the effect of the tunnel section shape on the crack propagation law of surrounding rock in adjacent tunnel under blast loading, detailed research is carried out by model test and extended finite element(XFEM). The experimental study shows that under the blast loading, when the original crack grows through the original crack tip zone of the adjacent tunnel surrounding rock, the circumferential tensile zone resulting from propagating stress wave and the reflection stretch zone under the influence of the adjacent free surface of the tunnel, the growth directions have a great difference. The section shape of the tunnel mainly affects the extension direction of the original crack at the later stages. When the section shape of tunnel is different, the direction of the tensile stress of the free-face reflection tensile wave is also different. Since the direction of the reflection tensile stress is generally perpendicular to the free surface, the original cracks in the surrounding rock of the straight wall archway tunnel and the circular tunnel grow along tangential to the curved free surface, and the approximate “layer crack” phenomenon appears. However, the original crack propagation direction of the surrounding rock of the rectangular tunnel is parallel to the direction of the tensile stress of the vertical plane reflection wave, and the crack propagation is not affected, and it is still penetrated into the free surface along the approximate horizontal direction.